Aplikasi Kelas Ibu Hamil sebagai upaya Rekronstruksi Budaya "Tarak" (Tidak Makan Makan Telur, Ayam, Daging dan Ikan) pada Ibu Nifas di Kabupaten Blitar - Zaenal Fanani; Bisepta Prayogi (Journal of Ners and Midwifery, 2014)
Indonesian peoples is a multicultural society. Each region has a distinct culture that is embraced by the trust from the previous generation ( Tommey and Alligood ,2006) . Based on a preliminary study of 20 post partum mothers, there are 17 people did not want to eat chicken dishes, meat and eggs for fear of the seams are not cured and itching . Protein is needed in the process of wound healing episiotomy and in breastfed infants, these conditions need to be an intervention . The purpose of this study was to determine the effect mother class of pregnant women to the knowledge, attitudes and behavior of post partum continence. Method: Research design was pretest and posttest nonequivalent control group with a sample of 40 people, who were divided into 20 groups and 20 controls of the treatment group. Sampling technique by using consecutive. The treatment group got mother class while the control group got health education as usual in health centers. In both groups was measured knowledge , attitudes , and behaviors " post partum continenceâ€. Results: The result of this study showed that on paired t test p = 0.000, that mean at treatment group change on knowledge before and after mother class. On control group showed that not change in knowledge with paired t test p = 0.083. In indepedentÂ  t test p = 0.000 there is a difference of knowledge between treatment groups and control groups. Paired t test p = 0.000 at the attitude shown that there is a change in attitude before and after treatment. In control group paired t test p = 0.163 indicates that there is no change in attitude. Independent t test p = 0.000 shows that there are differences in attitudes between the treatment and control groups . Chi-square test p = 0.000 on the behavior of incontinence, there are differences in the proportion of incontinence behavior between the treatment and control groups. Discussion:The research recommended mother class intervention for enhance knowledge, attitude and behavior for pregnant women of post partum incontinence culture.